INSTRUKSI EKSPLISIT DAN IMPLISIT DALAM LETTER OF CREDIT - Paniya, Paniya - (Admisi dan Bisnis, 2014)
As one of payment methods in international trade of goods, letter of credit is used more and more by exporters and importers all over the world. Letter of credit is commonly written as a text in English, which needs interpretation. The interpretation on L/C text also needs another text, i,e Uniform of Customs and Practice for Documentary Credit (UCP-DC) - an international publication by International Chamber of Commerce.Â  The failure in interpreting an L/C may cause financial loss for an exporter, an importer or paying bank, because the L/C contains instructions directly or indirectly for parties involved in the operative L/C. This article is written with 2 (two) aims. Firstly, it is aimed at interpreting both the implied and explicit instructions in letter of credit, and secondly at giving inspiration to English teachers to learn subjects other than English study. The first aim is unquestionable because the correct interpretation may lead to a success in flow of goods, documents of the goods, and payment. The second aim is crucial in relation to giving broader horizon to English teachers or lecturers, because English teachers are required to improve their knowledge when teaching commercial correspondence for international trade of goods (export-import of commodities). English teachers teachingÂ  commercial correspondence for international trade cannot only depend on their English knowledge, but also on their knowledge on international trade including